All there is to water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Land and water resources in the Caribbean Edited by C L Paul & J Opadeyi, Caribbean Agricultural Research and Development Institute (CARDI) and the University of the West Indies, 2001. 258 pp. ISBN 976 617 010 x US$ 15 Euro 15.20